Life, the universe, and everything - Adams, Douglas, 1952-2001.; Picador (London : Picador, 2002)
Arthur Dent and Ford Prefect learn why Earth has been shunned by the rest of the galaxy as they journey through space and time.
Originally published in the U.S. by Harmony Books, 1982.
Adult
Keywords: Dent, Arthur (Fictitious character) -- Fiction; Interplanetary voyages -- Fiction; Prefect, Ford (Fictitious character) -- Fiction; Dent, Arthur (Fictional character) -- Fiction; Prefect, Ford (Fictional character) -- Fiction; Science fiction; Fantastic fiction